Analysis Of Product Development To Increase Market Share At Roti Gembong Jagoan Mama Samarinda MSMEs - Kurniawan, Muhammad Rizal; Althalets, Faries (Jurnal Ekonomi, 2024)
This research aims to find out how the product development process is carried out by Roti Gembong Jagoan Mama. This thesis research methodology uses a qualitative approach whose research results are presented in descriptive form. For data collection, the author uses observation, interviews, and documentation. The results of the study are the type of product development carried out by Roti Gembong Jagoan Mama is product development in terms of flavor variants, with the initial stage of finding a product concept which will later create a new product, while the obstacles obtained by Roti Gembong Jagoan Mama in carrying out product development are the lack of benefits of technology and social media, the emergence of similar business competitors, and the increase in raw materials needed in product development, and the results obtained by Roti Gembong Jagoan Mama from carrying out product development are maintaining product quality, increasing the types of products sold, and maintaining consumer loyalty. In the indicator of business competition, namely the role of developing bread products carried out is the right strategy to face business competition, by developing products at Roti gembong Jagoan Mama in order to innovate the products offered to consumers of marketed products, and have good potential to face increasingly strong business competition, especially in the sale of bread in the city of Samarinda.